Assessment of Organ Dosimetry for Planning Repeat Treatments of High-Dose 131I-MIBG Therapy: 123I-MIBG Versus Posttherapy 131I-MIBG Imaging. (October 2017) - Pandit-Taskar, Neeta; Zanzonico, Pat; Hilden, Patrick; Ostrovnaya, Irina; Carrasquillo, Jorge A.; Modak, Shakeel
Abstract : Purpose: To evaluate detailed organ-based radiation-absorbed dose for planning double high-dose treatment with 131 I-MIBG. Methods: In a prospective study, 33 patients with high-risk refractory or recurrent neuroblastoma were treated with high-dose 131 I-MIBG. Organ dosimetry was estimated from the first 131 I-MIBG posttherapy imaging and from subsequent 123 I-MIBG imaging prior to the planned second administration. Three serial whole-body scans were performed per patient 2 to 6 days after 131 I-MIBG therapy (666 MBq/kg or 18 mCi/kg) and approximately 0.5, 24, and 48 hours after the diagnostic 123 I-MIBG dose (370 MBq/kg or 10 mCi/1.73 m 2 ). Organ radiation doses were calculated using OLINDA. 123 I-MIBG scan dosimetry estimations were used to predict doses for the second 131 I-MIBG therapy and compared with 131 I-MIBG posttherapy estimates. Results: Mean ± SD whole-body doses from 131 I-MIBG and 123 I-MIBG scans were 0.162 ± 112 and 0.141 ± 0.068 mGy/MBq, respectively. 123 I-MIBG and 131 I-MIBG organ doses were variable—generally higher for 123 I-MIBG–projected doses than those projected using posttherapy 131 I-MIBG scans. Mean ± SD doses to liver, heart wall, and lungs were 0.487 ± 0.28, 0.225 ± 0.20, and 0.40 ± 0.26, respectively, for 131 I-MIBG and 0.885 ± 0.56, 0.618 ± 0.37, and 0.458 ± 0.56, respectively, for 123 I-MIBG. Mean ratio of 123 I-MIBG to 131 I-MIBG estimated radiation dose was 1.81 ± 1.95 for the liver, 2.75 ± 1.84 for the heart, and 1.13 ± 0.93 for the lungs. No unexpected toxicities were noted based on 123 I-MIBG–projected doses and cumulative dose limits of 30, 20, and 15 Gy to liver, kidneys, and lungs, respectively. Conclusions: For repeat 131 I-MIBG treatment planning, both 131 I-MIBG and 123 I-MIBG imaging yielded variable organ doses. However, 123 I-MIBG–based dosimetry yielded a more conservative estimate of maximum allowable activity and would be suitable for planning and limiting organ toxicity with repeat high-dose therapies.